Digital transformation: Inevitable change or sizable opportunity? The strategic role of HR management in industry 4.0 - Teresa Galanti; Clara De Vincenzi; Ilaria Buonomo; Paula Benevene (Administrative Sciences, 2023)
Background: The impact of technologies on workers has been a recurring theme in occupational health psychology. In particular, the sudden digital transformation of the last two decades, accelerated by the COVID-19 pandemic, has stressed the urgency to investigate new ways of working that are characterized by flexibility and a constant increase of autonomy. In this perspective, this study aims to investigate the state of the art of the innovation process in Italian factories, explore whether and how digitalization can be seen as an opportunity, and imagine a new way of working characterized by adaptability, resilience, and openness to change. Methods: Thirty in-depth interviews of Italian experts in HR management were collected and analyzed using a mix-method approach. Results: The findings underline the Italian HR experts' perceptions of the risks associated with rapid changes required by technological progress in terms of workers' wellbeing and satisfaction and suggest how important it is that organizations rapidly set up learning and training programs to guide workers to the acquisition of new skills required by Industry 4.0. Conclusions: Future workplaces will be characterized by extreme versatility, which requires workers to increasingly have both technical and soft skills as well as the ability to collaborate and build functional relationships.
Keywords: 350; black swan; digitalization; HR management; human factor; Industry 4.0; look forward; training